THE IMPLEMENTATION OF CHARACTER-BASED ENGLISH LANGUAGE INSTRUCTION IN ENHANCING STUDENTS’ COMPETENCE AT MUHAMMADIYAH KWALA MADU ISLAMIC BOARDING SCHOOL - Sri Ramdhani (Hijri, 2026)
This study aims to examine the implementation of character-based English language learning in enhancing the competence of students at Muhammadiyah Kwala Madu Islamic Boarding School. The research is grounded in the importance of integrating character education values into language learning to foster not only linguistic proficiency but also positive attitudes and moral development among students. This study employs a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the implementation of character-based English learning is carried out through the integration of character values such as discipline, responsibility, cooperation, and respect within teaching activities. Teachers incorporate these values through interactive methods, including group discussions, role-plays, and daily English communication practices. The results indicate that this approach contributes significantly to improving students’ English competence, particularly in speaking and listening skills, while also strengthening their character development. n conclusion, character-based English language learning is effective in enhancing both students’ language competence and character formation. Therefore, it is recommended that educators consistently integrate character values into English language instruction, especially in Islamic boarding school contexts.